Jan Magne Gjerde og Mari Strifeldt Arntzen (red.): Perspectives on Differences in Rock Art - Heidrun Stebergløkken (Viking, 2021)
Bokanmeldelse av boka Jan Magne Gjerde og Mari Strifeldt Arntzen (red.): Perspectives on Differences in Rock Art.